The Camino Verde intervention in Nicaragua, 2004–2012 - Arosteguí, Jorge (BMC Public Health, 2017)
ABSTRACT: Camino Verde (the Green Way) is an evidence-based community mobilisation tool for prevention of dengue and other mosquito-borne viral diseases. Its effectiveness was demonstrated in a cluster-randomised controlled trial conducted in 2010–2013 in Nicaragua and Mexico. The Nicaraguan arm of the trial was preceded, from 2004 to 2008, by a feasibility study that provided valuable lessons and trained facilitators for the trial itself. Here, guided by the Template for Intervention Description and Replication (TIDieR), we describe the Camino Verde intervention in Nicaragua, presenting its rationale, its time and location, activities, materials used, the main actors, modes of delivery, how it was tailored to encourage community engagement, modifications made from the feasibility study to the trial itself, and how fidelity to the process originally designed was maintained. We also present information on costs and discuss the place of this study within the literature on implementation science. TRIAL REGISTRATION: ISRCTN27581154.